2020
DOI: 10.5650/jos.ess20031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Added Tetraalkylammonium Counterions on the Dilational Rheological Behaviors of N-Cocoyl Glycinate

Abstract: Ion specific effect, which was first reported by Hofmeister in 1888 1 , has been reported in tons of systems with charged interfaces or surfaces, including surfactant aggregates, supramolecular structures, enzymes, and polymers over the past several decades 2 5 . Counterions in added salts are an important factor affecting the intermolecular interaction, surface activity, micellization, and aggregate morphological transition of ionic surfactants. Various organic and inorganic counterions are often used because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Tetraalkylammonium ions, which are a group of kosmotropic cations, usually have profound effects on anionic surfactants. Previous studies have shown that such hydrophobic cations tend to induce the micellar growth of anionic surfactants . Using the chemical trapping (CT) method, we have shown that such transitions induced by TAA + , in AOT aqueous solutions, are accompanied by a marked rise in interfacial headgroup molarity and a decline in interfacial water molarity, which supports the specific ion-pair/hydration model .…”
Section: Introductionsupporting
confidence: 77%
“…Tetraalkylammonium ions, which are a group of kosmotropic cations, usually have profound effects on anionic surfactants. Previous studies have shown that such hydrophobic cations tend to induce the micellar growth of anionic surfactants . Using the chemical trapping (CT) method, we have shown that such transitions induced by TAA + , in AOT aqueous solutions, are accompanied by a marked rise in interfacial headgroup molarity and a decline in interfacial water molarity, which supports the specific ion-pair/hydration model .…”
Section: Introductionsupporting
confidence: 77%
“…Many more investigators have shown in recent years which organic counterions can improve the micellization functions of surfactants in the aqueous medium, for example, tetraethyl and tetra- n -propylammonium, n -alkyl carboxylate ions and tetraalkylammonium counterions. Our research groups are currently investigating the micellization properties of surfactants in the presence of organic additives such as ionic drugs, dyes, and polyelectrolytes in the aqueous medium. ,,,, …”
Section: Introductionmentioning
confidence: 99%